2013
DOI: 10.3233/bmr-130389
|View full text |Cite
|
Sign up to set email alerts
|

Educational status and knowledge level of pre- and postmenopausal women about osteoporosis and risk factors: A cross-sectional study in a group of Turkish female subjects

Abstract: Although half of the pre- and postmenopausal women reported having some awareness of OP, their level of knowledge was poor, particularly with regard to the risk factors associated with the condition and its complications. Having information about the risks of OP and a better understanding of the health beliefs of those at risk are important, as both may play a major role in influencing an individual's OP-preventing behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…The results of a study carried out in Vietnam showed that women with a high level of education had high osteoporosis knowledge levels (18). Another study conducted with premenopausal and post-menopausal women in Turkey reported that the women's osteoporosis knowledge level of was generally low, although the women with higher education level had higher knowledge levels (19). In a study conducted with women and men in the United States of America determined that the osteoporosis knowledge level increased with age; however, no relation was observed between the level of education and the osteoporosis knowledge level (20).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study carried out in Vietnam showed that women with a high level of education had high osteoporosis knowledge levels (18). Another study conducted with premenopausal and post-menopausal women in Turkey reported that the women's osteoporosis knowledge level of was generally low, although the women with higher education level had higher knowledge levels (19). In a study conducted with women and men in the United States of America determined that the osteoporosis knowledge level increased with age; however, no relation was observed between the level of education and the osteoporosis knowledge level (20).…”
Section: Discussionmentioning
confidence: 99%
“…Daha önce yapılan bir kaç çalışmada kırsal bölgede yaşayan kadınların osteoporozu önleme ile ilgili az miktarda bilgiye sahip oldukları gösterilmiştir (10,14,19,20). Ayrıca bizim çalışmamızda olduğu gibi eğitim seviyesinin farkındalığı arttırdığını gösteren çalışmalarda mevcuttur (13,21). Ancak daha önce kırsal bölgede yapılan çalışmalar ve bizim çalışmamızda da görüldüğü gibi kırsal bölgedeki kadın nüfusunun eğitim seviyesi düşük olduğundan farkındalığın da düşük olması beklenen bir sonuçtur (10,13,14).…”
Section: Discussionunclassified
“…Primera radi, istraživanje sprovedeno u Turskoj je ukazalo da su rezultati na uputnicima o znanju o osteoporozi veoma oskudna i da se nisu značajno razlikovala izmedju žena pre i posle menopauze. 15 Nedovoljno znanje o osteoporozi imaju i one žene u Brazilu koje su posle perioda menopauze već imale dijagnostikovanu osteopeniju ili razvijenu osteoporozu. 16 Slično tim saznanjima, istraživanje sprovedeno u Španiji je utvrdilo da tek nešto više od svake pete žene u postmenopauzi koje se leči od osteoporoze ima adekvatna saznanja o svojoj bolesti.…”
Section: Diskusijaunclassified
“…sugerisano da su više obrazovanje, bolji socioekonomski status, odsustvo komorbiditeta i mere farmaceutske zdravstvene nege verovatni povoljni činioci (Costa-Paiva et al, 2011; Okumus et al, 2013; Lai et al, 2013). 15,16,19 Ipak, kako su slična istraživanja u našoj zemlji raritetna, naši rezultati povećavaju stepen saznanja u ovoj oblasti čineći teorijsku osnovu za buduće studije, većeg obima, prospektivnog karaktera i detaljnijeg dizajna. Takodje, pre šire ekstrapolacije rezultata naše studije trebalo bi sprovesti istraživanja koja bi ukljućila populaciju drugih urbanih i ruralnih područjima Srbije, poželjno na populacionom niovu.…”
Section: Diskusijaunclassified